(untitled) (New York, 1993)
Written by more than 50 experts from around the world, this compendium of hydrologic theory and practice is a welcome and long overdue essential reference for all practicing hydrologists and related professionals. Packed with valuable information and expert guidance, the handbook offers solutions to your most perplexing on-the-job problems.For example, you'll learn how to: estimate the magnitudes of floods and mitigate their effects; develop solutions for cleaning up and preventing pollution of surface water and groundwater; assess water usage for a city or an irrigation project; choose reliable methods for urban drainage design; calculate the rate of rainfall, evaporation, infiltration, groundwater flow, snow-melt, and streamflow; determine the rate of movement of contaminants in surface water and groundwater; assess the hydrologic effects of land-use changes such as deforestation; statistically analyze hydrologic data, including extreme events, time series, and spatial data; select the best computer package for hydrologic simulation; and, use remote sensing, automated data collection, forecasting, and advanced computer methods in hydrology.Now when you need to understand an unfamiliar term or a new subject area, obtain a formula, find a computer program for solving a problem, obtain values from a map or a table of data, or convert hydrologic units, this is the only source you'll need. A must-have reference for anyone involved in hydrology, environmental pollution, urban drainage, water resources planning and management, and related fields, the "Handbook of Hydrology" will prove to be indispensable to your work.
Mô hình toán thủy văn
Keywords: Hydrology,Hydrology,Hydrology,Hydrology,Hydrology,Hydrology,Hydrology,Hydrology,Thủy văn; Handbooks, manuals, etc.,Handbooks, manuals, etc.,Handbooks, manuals, etc.,Handbooks, manuals, etc.,Handbooks, manuals, etc.,Handbooks, manuals, etc.,Handbooks, manuals, etc.,Handbooks, manuals, etc.,Sổ tay, sách hướng dẫn, v.v.